Tanya Bray letter and field report to Thomas H. Kent, November 29, 1982. - Bray, Tanyaet al (1982)
Field report was contributed by Tanya Bray and other observers in a letter to Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1982. Epson - sheet feed